Kalman-variant estimators for state of charge in lithium-sulfur batteries - Propp, Karsten; Auger, Daniel; Fotouhi, Abbas; Longo, Stefano; Knap, Vaclav (Cranfield University, 2022)
This fileset is a set of MATLAB/Simulink R2016a models implementing state-of-charge estimators for lithium-sulfur batteries as described in the associated publications. The associated experimental data is also included. Instructions are included in a 'readme.txt' file in the root directory.

This fileset is a set of MATLAB/Simulink R2016a models implementing state-of-charge estimators for lithium-sulfur batteries as described in the associated publications. The associated experimental data is also included. Instructions are included in a 'readme.txt' file in the root directory.
Keywords: lithium-sulfur battery'; 'state of charge'; 'extended kalman filter'; 'unscented kalman filter'; 'particle filter'; 'Engineering not elsewhere classified'